The Purposeful View of Asylum and its Rights in Islamic Law (Abhat Journal, 2023)
Praise be to God, we praise Him, we seek His help, we seek His guidance, we seek His forgiveness, we repent to Him, and we bear witness that there is no god but God, alone with no partner, and we bear witness that our Master Muhammad is His servant and Messenger - may God’s prayers and peace be upon him - and his family and companions. It dealt with the Maqasid view of asylum and its rights in Islamic law; It is an issue that opens the Islamic vision to human horizons and builds common human rights with different societies, highlighting the giving of Islamic law and its ability to grant humanity what it aspires to, as Islamic law is the religion of instinct.     This study examines the idea of the influence of the science of intentions on rights, and the possibility of adopting the intentional dimension as an influential matter in understanding human rights in general, and asylum rights in particular, and its analysis, and revealing the secrets of its meanings. Many questions began to be raised about the view of Islamic law on the issue of refugees, and whether asylum conflicts with Islamic concepts, and if not, what are the rights related to asylum towards refugees, and what is the concept of asylum in Islamic law? Asylum and request for protectionFrom this point of view, I decided that the subject of the research be in (the purposeful view of asylum and its rights in Islamic law).
Keywords: Asylum rights; Islamic Law.; Purposes